Avaliação multicriterial na definição de áreas protegidas, no município de Piedade - SP - Sumida, Simone Sayuri (2013)
Fragmentation, degradation of habitats, overexploitaton of species and introduction of exotic species are some of the main threats to biodiversity, as a consequence of the human consumption and expansion needs. The local preservation or preservation in situ , through the establishment of legally protected areas is one way to mitigate the expansion of these activities. Piedade municipality presents a set of favorable conditions to establish protected areas: the urbanization is relatively low, native forest remnants occupy approximately 25% of the municipal area, and there are two relevant protected areas with portions within its boundaries: the Environmental Protection Area of Itupararanga, in the northeastern part, and, the State Park of Jurupará, in the southeastern portion. The protected areas in general occupy extensive areas, with different patches, forming a landscape mosaic, and can be studied by Geospatial Technologies, specially through one of its main techniques, the Geographic Information System (GIS), which allows the aggregation of factors through different approaches. Multicriteria evaluation (MCE) is one of those approaches, which transforms and combines different factors, considering their relevance and their respective levels of influence on the production of solutions / alternatives for decision making. In this context, the purpose of this study was to define priority areas for protection, in the Piedade municipality, through the Multicriteria evaluation (MCE). The specific objective was to identify the importance and influence of the selected factors on the decision support process and to evaluate which methods of MCE is appropriated to this study: Weighted Linear Combination (WLC) or Ordered Weighted Averaging (OWA). We defined the criteria and theirs weights using the Participatory Technique. The result was one map of priority areas through WLC and two maps through OWA, with similar degrees of tradeoffs and different degrees of risk to the decision support. The methods (WLC and OWA) enable the definition of priority areas for protection, although the WLC proposes a less detailed solution, which can result in uncertainties in landscape planning. The OWA offers different solutions, considering the risk-taking and factors tradeoffs, providing a greater number of possible answers to the question of interest. The map with low risk-taking was the more appropriated to define priority areas for protection in the Piedade municipality, SP.